The evolving use of measurable residual disease in chronic lymphocytic leukemia clinical trials - Fisher, A.; Goradia, H.; Martinez-Calle, N.; Patten, PEM.; Munir, T. (Frontiers in Oncology, 2023)
Measurable residual disease (MRD) status in Chronic Lymphocytic leukaemia (CLL), assessed on and after treatment, correlates with increased progression-free and overall survival benefit. More recently, MRD assessment has been included in large clinical trials as a primary outcome and is increasingly used in routine practice as a prognostic tool, a therapeutic goal and potentially a trigger for early intervention. Modern therapy for CLL delivers prolonged remissions, causing read-out of traditional trial outcomes such as progression-free and overall survival to be inherently delayed. This represents a barrier for the rapid incorporation of novel drugs to the overall therapeutic armamentarium. MRD offers a dynamic and robust platform for assessment of treatment efficacy in CLL, complementing traditional outcome measures, and accelerating access to novel drugs. Here, we provide a comprehensive review of recent major clinical trials of CLL therapy, focusing on small molecule inhibitors and monoclonal antibody combinations that have recently emerged as the standard front-line and relapse treatment options. We explore the assessment and reporting of MRD (including novel techniques), the challenges of standardisation and provide a comprehensive review of the relevance and adequacy of MRD as a clinical trial endpoint. We further discuss the impact that MRD data has on clinical decision making and how it can influence patient experience. Finally, we evaluate how upcoming trial design and clinical practice is evolving in the face of MRD-driven outcomes.